Cannabis in Thailand’s Transitional Era: a Health and Social Perspectives - ศิริไทย นภินทร; พูลพอกสิน วรรณวดี (Journal of Health Science of Thailand, 2025)
Thai allowing cannabis to be legally used in 2022 is a change that affects the awareness and the widespread opposition of those involved in society. This article aims to 1. study new meanings for cannabis in the transitional era of Thai society and 2. study suggestions on the utilization of cannabis. By reviewing documents and in-depth interviews with 10 people involved and using content analysis. The results are as follows: Thai society perceived and defined cannabis in the transitional era are found in four main discourses: (1) “Cannabis is a narcotic” based on the idea that it is harmful and Illegal; (2) “Medical cannabis” emphasizing the health dimension with the idea that cannabis is wisdom and has more benefits than harm. There must be support for studying the benefits and harms of medical cannabis and studying Thai traditional and folk medical cannabis based on evidence. (3) "Cannabis is the new Economic crop.” focusing on the economic dimension. There is a lot of support from the people and the political sector has implemented to support. However, there must be support for studies for the development of cannabis based on economic systematic and guidelines to regulating the utilization of cannabis and cannabis policies for the benefit of the Thai economy. And (4) “Recreational cannabis free” emphasizes the rights and liberties and use for recreation freely. It must support the communication of cannabis knowledge and facts. However, the above discourse on cannabis has the same perception and understanding to cannabis is both beneficial and harmful. It depends on the purpose of utilization. Public spaces and participation must be provided for the design of the direction of Thai cannabis policy.